“Analysis of Penanian Dolo Musical Composition Entitled: Ia Ke Ka’tumo Tu Sunga’ku” (Universitas Negeri Semarang, 2022)
This study discusses the art forms in Toraja cultural rituals, which are more precisely held in Lembang Gandangbatu, Gandangbatu Sillanan District. The ritual is called Ma'bulle Tomate. The Ma'bulle Tomate ritual is an activity of carrying the corpse to the burial place. The community performs the Ma'bulle Tomate ritual while singing a spiritual song called Penanian Dolo. This study aims to reveal the structure of the Penanian Dolo musical composition entitled Ia Ke Ka'tumo tu Sunga'ku as one of the songs in the funeral ritual. This research is qualitative research using musicology and sociology approaches. It was conducted in Lembang Gandangbatu, Gandangbatu Sillanan District, Tana Toraja Regency. Data was obtained through observation, interviews, and documentation. The data obtained were then analyzed using qualitative data analysis techniques: data reduction, data presentation, and conclusions. The results of this study explain that the musical composition of Penanian Dolo entitled Ia Ke Ka'tumo tu Sunga'ku belongs to the form of a two-part song with symmetrical sentence pieces (AA'BA'). Like a hymn song that has simple melodic movements and is easy to learn and remember, that is the character of the song Ia Ke Ka'tumo tu Sunga'ku. The community's interpretation of singing the song Ia Ke Ka'tumo Tu Sunga'ku uses a 6/4 time rhythm pattern with an Adagietto tempo which means slow with a speed of 63-69 beats per minute. The heart-rending recitation of the verses and the resulting three-voice harmony can bring a sad and gripping feel, even though the song does not start with a minor chord. This research would be an effort and contribution of thought in the form of written works as a form of preserving Toraja cultural music as well as adding insight into the art of music in Indonesia.